Diagnostic significance of nitric oxide concentrations in exhaled air from the airways in allergic rhinitis patients - Kłak, Anna; Krzych-Fałta, Edyta; Samoliński, Bolesław K.; Zalewska, Marta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : The effect of nitric oxide (NO) on the human body is very important due its physiological regulation of the following functions of airways: modulation of ciliary movement and maintenance of sterility in sinuses. Aim: To evaluate the diagnostic significance of NO concentrations in exhaled air from the upper and lower airways in patients diagnosed with allergic rhinitis (AR). Material and methods: The subjects included in the study were a group of 30 people diagnosed with sensitivity to environmental allergens and a control group consisting of 30 healthy subjects. The measurement of NO in the air exhaled from the lower and upper airways was performed using an on-line method by means of Restricted Exhaled Breath (REB), as well as using the measurement procedure (chemiluminescence) set out in the guidelines prepared in 2005 by the American Thoracic Society and the European Respiratory Society. Results: In the late phase of the allergic reaction, higher values of the level of exhaled NO concentration from the lower airways were observed in the groups of subjects up to the threshold values of 25.17 ppb in the group of subjects with year-round allergic rhinitis and 21.78 ppb in the group with diagnosed seasonal allergic rhinitis. The difference in the concentration of NO exhaled from the lungs between the test group and the control group in the 4th h of the test was statistically significant (p = 0.045). Conclusions : Exhaled NO should be considered as a marker of airway inflammation. It plays an important role in the differential diagnosis of allergy.